Efficacy, safety and acceptability of the new pen needle 33G × 4 mm. AGO 01 study. (March 2015) - Valentini, M.; Scardapane, M.; Bondanini, F.; Bossi, A.; Colatrella, A.; Girelli, A.; Ciucci, A.; Leotta, S.; Minotti, E.; Pasotti, F.; Pesenti, A.; Rocca, L.; et al.
Abstract Objectives: Adherence to insulin therapy can be threatened by pain and needle fear. This cross-over randomized non-inferiority trial evaluated a new Pic Insupen 33G × 4 mm needle vs. a 32G × 4 mm needle in terms of metabolic control, safety and acceptability in patients with diabetes treated with insulin. Research design and methods: We used a centralized, permuted block randomization, stratified by center and maximum insulin dose per single injection. Subjects used the two needles in two 3 week treatment periods. The primary endpoint was the absolute percentage variation of the blood fructosamine between the two treatments (% |ΔFru|). Additional endpoints were: glycemic variability, total insulin doses, body weight, severe hypoglycemic episodes, leakage at injection sites and pain measured by visual analogue scale. Equivalent glycemic control was defined a priori as % |ΔFru| (including 95% CI) within 20%. Results: Of 87 subjects randomized, 77 completed the study (median age 53.1 [IR 42.3–61.2], median BMI 24.3 Kg/m2 [IR 21.3–28.5], median duration of insulin therapy [in months] 141.4 (IR 56.3–256.9), median baseline HbA1c 7.9% [IR 7.2–8.8]). The % |ΔFru| was 7.93% (95% CI 6.23–9.63), meeting the non-inferiority criterion. The fasting blood glucose standard deviation was 46.2 (mean 154.6) with the 33G needle and 42.8 (mean 157.3) with the 32G needle (p = 0.42). Insulin daily dose and patients' weight did not show any statistically significant variation. We observed 95 episodes of symptomatic hypoglycemia with the 33G needle and 96 with the 32G needle. One episode of severe hypoglycemia was documented in the latter group. As for insulin leakage we observed 37.55 episodes per 100 patient-days with the 33G needle and 32.21 episodes per 100 patient-days with the 32G needle (p = 0.31). Patients reported less pain with the 33G × 4 mm needle (p = 0.05). Study limitations: Study sample was mainly composed of adults with type 1 diabetes and study was not blinded. Conclusions: The 33G needle is not inferior to the 32G needle in terms of efficacy and safety, with reduced pain and no difference in insulin leakage. Clinical trial registration: NCT01745549.